Zibotentan in systemic sclerosis-associated chronic kidney disease: a phase II randomised placebo-controlled trial - Edward P. Stern; Lauren V. Host; Ivy Wanjiku; K. Jane Escott; Peter S. Gilmour; Rachel Ochiel; Robert Unwin; Aine Burns; Voon H. Ong; Helen Cadiou; Aidan G. O’Keeffe; Christopher P. Denton (Arthritis Research & Therapy, 2022)
Abstract Background We report results from a phase II randomised placebo-controlled trial assessing zibotentan, a highly selective endothelin receptor antagonist (ERA), in chronic kidney disease (CKD) secondary to systemic sclerosis (SSc). Methods This trial included three sub-studies: ZEBRA 1—a randomised placebo-controlled, double-blind trial of zibotentan in SSc patients with CKD2 or CKD3 (and glomerular filtration rate (GFR) >45 ml/min) over 26 weeks; ZEBRA 2A—a 26-week placebo-controlled, single-blind trial of zibotentan in scleroderma renal crisis patients not requiring dialysis; and ZEBRA 2B—an open label pharmacokinetic study of zibotentan in patients on haemodialysis. Results Sixteen patients were screened for ZEBRA 1. Of these, 6 patients were randomised to zibotentan and 7 to placebo. In ZEBRA 1, there were 47 non-serious adverse events (AE) during the trial. Twenty-seven occurred in the placebo group and 20 in the zibotentan group. One serious adverse event (SAE) occurred during ZEBRA1, in the placebo arm. Descriptive statistics did not suggest an effect of study drug on serum sVCAM1. Estimated GFR numerically declined in patients treated with placebo at 26 weeks and 52 weeks. In contrast, average eGFR increased in zibotentan-treated cases. The 4 patients in ZEBRA 2A experienced 8 non-serious AEs, distributed equally between placebo and zibotentan. There was one SAE each in placebo and zibotentan groups, both unrelated to study medication. ZEBRA 2B recruited 8 patients, 6 completed first dosing, and 2 completed a second dosing visit. Pharmacokinetic analysis confirmed zibotentan levels within the therapeutic range. Three patients experienced 3 non-serious AEs. One SAE occurred and was unrelated to study drug. Conclusions Zibotentan was generally well-tolerated. ZEBRA 1 did not show any effect of zibotentan on serum sVCAM-1 but was associated with numerical improvement in eGFR at 26 weeks that was more marked at 52 weeks. ZEBRA 2B suggested a feasible dose regimen for haemodialysis patients. Trial registration EudraCT no: 2013-003200-39 (first posted January 28, 2014) ClinicalTrials.gov Identifier: NCT02047708 Sponsor protocol number: 13/0077